Effectiveness of physical activity interventions for overweight and obesity during pregnancy: a systematic review of the content of behaviour change interventions - Caragh Flannery; Milou Fredrix; Ellinor K. Olander; Fionnuala M. McAuliffe; Molly Byrne; Patricia M. Kearney (BMC, 2019)
Abstract Background Behaviour change techniques (BCTs) employed within PA intervention for pregnant women with a healthy body mass index (BMI) have been previously identified, however, these BCTS may differ for other weight profiles during pregnancy. The aim of this current review was to identify and summarise the evidence for effectiveness of PA interventions on PA levels for pregnant women with overweight and obesity, with an emphasis on the BCTs employed. Methods A systematic review and meta-analysis of PA intervention studies using the PRISMA statement was conducted. Searches were conducted of eight databases in January 2019. Strict inclusion/exclusion criteria were employed. The validity of each included study was assessed using the Cochrane Collaboration's tool for assessing risk of bias. The primary outcome measure was change in PA levels, subjectively or objectively measured, with physical fitness as a secondary outcome. All intervention descriptions were double coded by two authors using Michie's et al's BCT taxonomy V1. Meta-analyses using random effect models assessed the intervention effects on PA. Other PA outcomes were summarised in a narrative synthesis. Results From 8389 studies, 19 met the inclusion criteria 13 of which were suitable for inclusion in a meta-analysis. The remaining 6 studies were described narratively due to insufficient data and different outcome measures reported. In the meta-analysis, comparing interventions to a control group, significant increases were found in the intervention group for metabolic equivalent (SMD 0.39 [0.14, 0.64], Z = 3.08 P = 0.002) and physical fitness (VO2 max) (SMD 0.55 [0.34, 0.75], Z = 5.20 P = < 0.001). Of the other six, five studies reported an increase in PA for the intervention group versus the control with the other study reporting a significant decrease for women in their 3rd trimester (p = 0.002). 'Self-monitoring of behaviour' was the most frequently used BCTs (76.5%), with 'social support' being newly identified for this pregnant population with overweight or obesity. Conclusions This review identified a slight increase in PA for pregnant women with overweight and obesity participating in interventions. However, due to the high risk of bias of the included studies, the results should be interpreted with caution. PA measures should be carefully selected so that studies can be meaningfully compared and standardised taxonomies should be used so that BCTs can be accurately assessed.